If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (x + 1) + (x + 2) = 3(x + 2) Reorder the terms: X + (1 + x) + (x + 2) = 3(x + 2) Remove parenthesis around (1 + x) X + 1 + x + (x + 2) = 3(x + 2) Reorder the terms: X + 1 + x + (2 + x) = 3(x + 2) Remove parenthesis around (2 + x) X + 1 + x + 2 + x = 3(x + 2) Reorder the terms: 1 + 2 + X + x + x = 3(x + 2) Combine like terms: 1 + 2 = 3 3 + X + x + x = 3(x + 2) Combine like terms: x + x = 2x 3 + X + 2x = 3(x + 2) Reorder the terms: 3 + X + 2x = 3(2 + x) 3 + X + 2x = (2 * 3 + x * 3) 3 + X + 2x = (6 + 3x) Solving 3 + X + 2x = 6 + 3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + X + -3 + 2x = 6 + -3 + 3x Reorder the terms: 3 + -3 + X + 2x = 6 + -3 + 3x Combine like terms: 3 + -3 = 0 0 + X + 2x = 6 + -3 + 3x X + 2x = 6 + -3 + 3x Combine like terms: 6 + -3 = 3 X + 2x = 3 + 3x Add '-2x' to each side of the equation. X + 2x + -2x = 3 + 3x + -2x Combine like terms: 2x + -2x = 0 X + 0 = 3 + 3x + -2x X = 3 + 3x + -2x Combine like terms: 3x + -2x = 1x X = 3 + 1x Simplifying X = 3 + 1x
| 4y+3x=1800 | | 2x^2+15x+9=2 | | 63/98 | | 10y-2x=-8 | | -31-4x=-5-5(1+x) | | 3x+4y=1800 | | (36y^6-24y^3)/4y^3 | | 5y-14+3y+8=90 | | 7y-1+2y+10=90 | | (3y-5)+(8x-5)+(5x-10)=115 | | 15x^2-32x-60=0 | | F(n)=3n^2+4n | | (3y-5)+(8x-5)+(5x-10)=360 | | log2base1/4 | | 9x-11=7x+11 | | 12a-3=3a+15 | | 5x-3y+8=3(x-8) | | 4(5+x)=5(3x-1)-63 | | y=.34x+41 | | -3(x+2)+4=5(x+3)+9 | | 12a-1=a+5 | | 4x-(-x+3)+3=5-2(3-4x) | | 4x[33-3x(5+2)]= | | 4x+3(3-2x)=3(-2+2x)-3x-7 | | 2x+4.7=7.5 | | r^2=-40+13r | | 3x-17=-32 | | (2/5)(1/5) | | 2b+4=-17.2 | | 8=4(7x+3) | | x-47-4x=5-7x-19+3x | | 2x-12x^2+32=0 |